THE AIMS AND OBJECTIVES OF RELIGIOUS STUDIES - Ashurov N. B. (European Science Publishing, 2024)
Religious Studies is an interdisciplinary academic field that seeks to explore the diverse dimensions of religion, including its beliefs, practices, texts, and societal impact. The primary aim of Religious Studies is to foster a deeper understanding of the various religious traditions that shape human history and culture, promoting tolerance, empathy, and interfaith dialogue. It examines how religion influences social structures, politics, ethics, and cultural identity, while also encouraging academic inquiry into religious phenomena. By employing a range of disciplines such as history, anthropology, sociology, psychology, and theology, Religious Studies provides valuable insights into the role of religion in modern society and its interactions with contemporary issues. The field also emphasizes the importance of critical thinking, encouraging students to analyze and interpret religious texts and practices from diverse perspectives. Ultimately, Religious Studies contributes to a more comprehensive understanding of the complex relationship between religion and human civilization.
Keywords: Religious Studies, religious tolerance, academic inquiry, religious practices, comparative religion, interdisciplinary approach, sacred texts, religious institutions, modernity, critical thinking.